Pancreatic pseudocyst: a rare presentation - Nikitha Abirami B.; Anitha P.; Saji James; Mahalakshmi Mahalakshmi (Pediatric Review: International Journal of Pediatric Research, 2020)
Pseudocyst formation is defined as a localised collection of pancreatic juice enclosed by a wall of fibrous or granulation tissue arising as a result of acute and chronic pancreatitis or pancreatic trauma. They are more commonly found in men than women and are solitary in most cases. Mostly occurs in lesser sac and peripancreatic region. Thoracic / mediastinal the extension is rare. About 100 cases have been reported in literature. The pathogenicincludesism involved in the formation of pleural effusion include direct contact of pancreatic enzymes with the diaphragm, haematogenous transfer of pancreatic enzymes into pleura, transfer of pancreatic secretions through trans diaphragmatic lymphatics and results in the formation of pancreatico pleural fistula which results in direct communication of pancreatic pseudocyst within the pleural cavity. The clinicopathologic features of the cyst include a cystic wall without an epithelial cell lining and a black cystic fluid with high amylase concentration. Pseudocyst persisting for longer than 6 weeks have been associated with three folds increases in complication rates. The complications of pseudocyst include infection, haemorrhage, obstruction, rupture and erosion into neighbouring structures including major blood vessels. Pancreatic fistula and ascitis result when there is leakage or rupture of pseudocyst into the abdominal cavity. Repeated pleural effusion presumably resulting from rupture and fistulation from pancreatic duct initial account the pleural cavity. Such presentation account for less than 3 % of cases and even rarer to be an asymptomatic event. Resection is the optimal treatment for persistent leakage from the tail of pancreas. The diagnosis requires the careful integration of many historical, radiographic, laboratory, and other factors, and management is markedly different depending on the type, location and size of cystic lesion of pancreas. We report this case of rare location of pseudocyst i.e. thoracoabdominal without any ductal communication.